Implementasi Keterampilan Abad 21 Berbasis Kurikulum Merdeka Pembelajaran IPAS Menggunakan Model Project Based Learning (PjBL) pada Siswa Kelas V SDN 1 Damar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the implementation of 21st-century skills based on the independent curriculum for science learning using the Project Based Learning (PjBL) model for fifth-grade students of SDN 1 Damar, specifically on the food chain topic. The study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that the implementation of the Project Based Learning (PjBL) model was able to increase student activeness in the learning process through direct involvement in every stage of the project, from planning, implementation, to presentation of results. Students gained a better understanding of the food chain concept contextually, developed creativity, critical thinking skills, collaboration, and a sense of responsibility for group assignments. In addition, the teacher's role as a facilitator contributed significantly to creating a conducive and meaningful learning environment. Thus, the implementation of the Project Based Learning (PjBL) model in science learning is in line with the principles of the Independent Curriculum which emphasizes student-centered learning and strengthening 21st-century skills.